La inteligencia artificial en el control del tránsito vehicular en la cuidad de Babahoyo, provincia de Los Ríos. - Alegría Espinoza, Alfredo Tomas (2023)
The present case study "Artificial Intelligence in the control of vehicular traffic in the city of Babahoyo, province of Los Ríos", is of the documentary and bibliographic type where the importance of applying different tools provided by artificial intelligence is analyzed to help to control mobility and vehicular traffic, trying to avoid traffic accidents and protect the lives of passers-by. The data provided by the National Traffic Agency, the mobility regulatory body in Ecuador, show that the vast majority of traffic accidents occur due to the recklessness of the driver when driving his vehicle, either due to disrespect for traffic signals, or for not taking basic safety measures when driving, this also shows that the majority of vehicles involved in these accidents are motorcycles. Artificial intelligence provides technological tools such as autonomous agents, intelligent systems, neural networks, computer vision, which makes it possible to identify and punish traffic law offenders, both the driver and the vehicle, monitor the flow of traffic and through this procedure established to improve the viability.